족관절 내측부 골관절염에서 과상부 절골술의 치료: 최신 경향 - 김우섭; 정홍근; Woo Sub Kim; Hong-Geun Jung (대한족부족관절학회지, 2025)
Ankle osteoarthritis, often arising from previous trauma, is characterized by progressive cartilage loss, joint space narrowing, and functional impairment, predominantly affecting younger, active individuals. A supramalleolar osteotomy (SMO) offers a joint-preserving surgical approach for cases with varus or valgus malalignment, aiming to redistribute the load across the tibiotalar joint. This review outlines the main surgical techniques (medial opening wedge, lateral closing wedge, and dome osteotomy) while addressing the debated role of a concomitant fibular osteotomy. The clinical outcomes from recent systematic reviews indicate significant improvement after an SMO in pain, function, and radiographic parameters, with relatively low complication and failure rates. Despite this, evidence remains limited by the retrospective study designs and inconsistent methodologies. Further high-quality prospective studies will be needed to standardize the indications, correction targets, and long-term outcomes for SMO.